Terapia con sedación paliativa en pacientes terminalmente enfermos : experiencia de una institución en Colombia. - Lombana Quiñónez, Milton Alberto; Santacruz, Juan G.; Pino, Luis; Camacho, María I.; Acevedo, Andrés; Buendía, María J.; Zamora, Ivonne; Torres, Ana; Méndez, Catalina; Cardona Zorrilla, Andrés Felipe (Revista Colombiana de Hematología y Oncología, 2017)
Background. Around 50% of advanced-stage cancer patients have inadequate control of symptoms during the final period of life; palliative sedation (PS) would seem to be appropriate in such scenario.